A Visual Interactive Analytics Interface for Complex Event Processing and Machine Learning Processing of Financial Market Data - Tri Luong, Nhan Nathan; Milosevic, Zoran; Berry, Andrew; Rabhi, Fethi (Proceedings / International Conference on Information Visualisation, 2020)
Applying machine learning techniques over streaming data is notoriously difficult as it involves the interplay of several technologies that need to be judiciously put together by IT experts. This has motivated the need to provide intuitive and easy to use interactive interfaces for financial experts to be able to leverage both Complex Event Processing (CEP) and Machine Learning (ML) technologies. The solution proposed in this paper is based on an open architecture that uses CEP engines as a pre-processing function for downstream ML training and prediction computations. We demonstrate this approach using a few scenarios involving the analysis of financial market data streams.